(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): In automotive business many risk-involved situations occur and when detected, an escalation process takes place. Although defined and controlled by process guidelines and being supported by experts, escalation brings increased emotional pressure and stress for parties involved. Do escalation processes in automotive industry maintain all implied challenges? Purpose: The purpose of the article is to present current status of escalation processes and gaps between theory and practice cases. Results of the analysis are recommendations of good engineering practice derived also from actual experiences and learned lessons. Method: The method involves analysis of practical cases from automotive development process, lessons learned, anonymous survey of automotive engineers and classification of experiences. Results: Results of the survey have shown that the controlled escalation process for know-how related escalations is needed in order to establish the environment where the team is able to provide new, sometimes unconventional ideas for the problem to be solved. Organization: Presented recommendations and measures enable organization and managers to put the expertise and experiences of employees into action for problem solving during escalation. Originality: In this article some practices are presented that, although simple and some yet seen, with proper adjustment stemming from real life processes give a fruitful settlement of escalations in automotive development business.